Development of VTOL-configured unmanned aquatic vehicle for underwater welding applications: An innovative design and multi-perspective computational investigations - Janani Priyadharshini Veeraperumal Senthil Nathan; Manikandan Arumugam; Mahendran Rajendran; Laxana Sourirajan; Gopinath Vinayagam; Akhila Ajith Pisharam; Sundhar Baskar; Beena Stanislaus Arputharaj; Subhav Singh; Khristina Maksudovna Vafaeva; Vijayanandh Raja (Results in Engineering)
Underwater welding is a challenging and intricate technique. An Unmanned Underwater Vehicle (UUV) has been specifically created for this task. This study encompasses all the calculations and computational techniques related to both the basic UUV and the UUV equipped with the underwater welding mechanism. The design and construction of this UUV are influenced by the hydrodynamic efficiency of fish, specifically Rhinaancylostoma. The identification of the unique parts, such as the wing, stabilizers, propellers, and fuselage welding equipment, is also achieved using conventional analytical methods. An examination of the suggested model using hydrodynamics has been conducted for both the forward and the Vertical Take-Off and Landing (VTOL) cases. The magnitudes of the forces exerted in all directions around the UUV with the welding mechanism are also recorded. A UUV was constructed, and hydrodynamic evaluations were carried out to address the challenges encountered during underwater welding. The distributions of pressure and velocity, as well as the forces acting in all three directions, are part of the outcomes of the hydrodynamic analysis. A maximum pressure of 3329.160 Pa and a maximum velocity of 3.989 m/s is achieved in the forward scenario, with a minimum total deformation of 0.0561 mm. There is a maximum velocity of 6.119 m/s and a maximum pressure of 4940 Pa in the VTOL scenario, in addition to the least deformation of 0.126 mm, when compared to the analysis performed amidst the other materials. With its minimal overall deformation, equivalent elastic strain, and strain energy of, GY 70 Epoxy stands out as the optimal material choice for both forward and VTOL cases. Following the study, it is evident that the suggested model is capable of effectively addressing the stated problem of performing underwater welding operations in underwater environments, autonomously and effectively.